Analisis Kritis terhadap Paradigma dan Kerangka Dasar Kebijakan Ketahanan Pangan Nasional - Pantjar Simatupang (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2007)
EnglishAn effective and efficient national food security strategy and policy can only be formulated using an appropriate paradigm. Food security paradigm evolves as food security context changes and in line with development of scientific understanding of the issue. This paper discusses evaluation of the food security paradigm and their application in designing strategy and framework of food security policy in Indonesia. It is shown that the national food sufficiency-oriented policy belongs to the food availability approach which has been empirically proven can not assure household or individual food security. The more appropriate paradigm is the food entitlement approach. Based on this paradigm, national food security strategy and policy should be designed comprehensively that includes food availability, access and utilization dimensions, and risk mitigation related to the three dimensions in an integrated macro-micro scale.IndonesianStrategi kebijakan ketahanan pangan nasional yang efektif dan efisien hanya dapat dirumuskan bila didasarkan pada paradigma yang tepat. Paradigma ketahanan pangan terus berkembang seiring dengan perubahan konteks permasalahan dan perkembangan pemahaman ilmiah. Tulisan ini menguraikan evolusi perkembangan paradigma ketahanan pangan dan penerapannya dalam perumusan strategi dan kerangka kerja kebijakan ketahanan pangan di Indonesia. Diungkapkan bahwa kebijakan yang berorientasi pada swasembada pangan termasuk ketegori paradigma pendekatan pengadaan pangan (food availability approach) yang secara empiris terbukti tidak menjamin ketahanan pangan keluarga atau individu. Paradigma yang lebih sesuai ialah pendekatan perolehan pangan (food entitlement approach). Untuk itu perlu disusun kebijakan komprehensif yang mencakup dimensi pengadaan, akses dan penggunaan pangan serta mitigasi atas risiko ketiga dimensi tersebut dalam skala makro-mikro terpadu.